2012
DOI: 10.4028/www.scientific.net/amr.599.326
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Influence of C/N Ratio on Denitrification Efficiency in CRI System

Abstract: Abstract. The TN removal efficiency is very low and the TN concentration of effluent can not meet the national standard of GB18918-2002 in the CRI system. In order to increasingly improve the denitrification efficiency of the CRI system, the artificial soil column is used to simulate the CRI system with 4 kinds of wastewater step-feeding modes. A series of comparative experiments are carried out, and the experimental results show that the TN removal efficiency of the CRI system is controlled by the denitrifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In electrochemical test, the solid-state supercapacitor showed anIntroductionAs to flexible conductive substrate, nickel foam has aroused many interests for loading of active materials in supercapacitor application, mainly due to its very good conductivity and 3D network structure that would reduce the diffusion resistance of electrolyte and provide ideal electron pathway. Besides, nickel foam can load more active materials per unit area than flat substrate (such as FTO and Ni foil) and it is also a commercialized cheap material 28,36,56,57,90,161,165,166. By XPS and CV measurements, research efforts have found Ni foam surface is mostly metallic in nature, while long-time exposing to moist air will result in passivated and metallic sections on the surface, which make Ni foam stable even under high temperature annealing in an oxidizing environment 167 .…”
mentioning
confidence: 99%
“…In electrochemical test, the solid-state supercapacitor showed anIntroductionAs to flexible conductive substrate, nickel foam has aroused many interests for loading of active materials in supercapacitor application, mainly due to its very good conductivity and 3D network structure that would reduce the diffusion resistance of electrolyte and provide ideal electron pathway. Besides, nickel foam can load more active materials per unit area than flat substrate (such as FTO and Ni foil) and it is also a commercialized cheap material 28,36,56,57,90,161,165,166. By XPS and CV measurements, research efforts have found Ni foam surface is mostly metallic in nature, while long-time exposing to moist air will result in passivated and metallic sections on the surface, which make Ni foam stable even under high temperature annealing in an oxidizing environment 167 .…”
mentioning
confidence: 99%